2023
DOI: 10.1590/1517-7076-rmat-2023-0003
|View full text |Cite
|
Sign up to set email alerts
|

Crushing performance of pultruded GFRP angle section with various connections and joints on lattice towers

Abstract: The significant features of the GFRP angle make it one of the modern construction members for the present lattice-type Transmission Line Towers (TLT) made out of mild steel. The GFRP structural angle members with gusset plate connections for net-crushing strength are investigated in this study, with an emphasis on connections to transmission line towers. Forty-two specimens of single-lap, butt joints with bolted connections are considered in this study. The gusset plate and edge distance have different widths.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Because the existing literature has indicated that these percentages may be used without substantial reduction, the high percentages of 25% and 35% were chosen [40][41][42][43][44]. In order to assess the economic viability of this substitution, the physical behaviour of the new concrete was compared to the cost [45].…”
Section: Materials and Methodologymentioning
confidence: 99%
“…Because the existing literature has indicated that these percentages may be used without substantial reduction, the high percentages of 25% and 35% were chosen [40][41][42][43][44]. In order to assess the economic viability of this substitution, the physical behaviour of the new concrete was compared to the cost [45].…”
Section: Materials and Methodologymentioning
confidence: 99%
“…The detailing figure of the rectangular beam is shown in Figure 1. By using the concrete mixer, the mixing is done, and the beams were kept for 28 days curing [40]. The plywood sheet mould is used for making beam specimens with the size of 170 mm × 250 mm × 1400 mm [41].…”
Section: Preparation Of Beam Specimenmentioning
confidence: 99%
“…The displacement was noted at each load point to draw the hysteresis loop. Strains in the reinforced bars were also monitored using an electrical resistance strain gauge [56]. Lacing angle 45°Closed stirrups 90°D iameter of cross rod (mm) 16 16 Span of beam (m) 0.66 0.66…”
Section: Experimental Programmentioning
confidence: 99%